Impact of grassland afforestation with contrasting tree species on soil phosphorus fractions and alkaline phosphatase gene communities. (August 2021) - Chen, Xiaodong; Condron, Leo M.; Dunfield, Kari E.; Wakelin, Steven A.; Chen, Lijun
Abstract: While grassland afforestation can enhance the net mineralization of soil organic phosphorus (P), the mechanisms involved and impacts of different tree species are not clear. Soil samples were taken from replicated adjacent field plots that had been maintained under unfertilized grazed grassland, radiata pine ( Pinus radiata ), and eucalyptus ( Eucalyptus nitens ) for 19 years. Soil phosphorus fractions were determined together with alkaline phosphatase activity and associated phoD and phoX gene analysis. Afforestation significantly decreased soil organic P, microbial biomass P, and soil alkaline phosphatase activity, and increased inorganic P bioavailability, although no differences were measured between radiata pine and eucalyptus. While distinct separation of phoD and phoX gene bacterial communities was associated with afforestation of grassland, separation between tree species was less pronounced. Shifts in phoD and phoX gene community structure were more related to soil moisture and pH than P status. Overall, we found that changes in soil moisture and pH associated with afforestation, rather than tree species per se, significantly affected the occurrence and diversity of bacterial alkaline phosphatase. This highlights the potential effects of changes in land-use and management on soil P dynamics and bioavailability. Highlights: Grassland afforestation caused significant reallocation mineralization of organic P. phoD and phoX bacterial genes communities were changed by afforestation. Soil moisture and pH determined the diversity of bacterial phosphatase genes.